PREVALENCE AND SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH SEDENTARY BEHAVIOR IN ADOLESCENTS FROM RIO CLARO-SP, BRAZIL - Christofoletti, Ana Elisa Messetti [UNESP]; Benites, Larissa Cerignoni; Sebastião, Emerson; Ueno, Deisy Terumi [UNESP]; Nakamura, Priscila Missaki (Universidade Estadual de Maringá, 2020)
The objective of this study was to analyze the prevalence of and sociodemographic factors associated with sedentary behavior (SB) situations among adolescents from Rio Claro, São Paulo, Brazil, namely: (1) obligations; 2) computer/tablet and video game; 3) smartphone; 4) television; 5) total SB. It included 482 teenagers (14.4 ± 2.1 years old) from 3 public and 2 private schools. They were assessed through an identification, clinical history and socioeconomic level questionnaire; Sedentary Behavior Questionnaire, with additional questions related to SB and use of smartphones and video games; Habitual Physical Activity Questionnaire for Adolescents; and weight and height measurement for Body Mass Index (BMI) calculation (kg/m²). Descriptive analysis was performed, Student’s t test was run to compare SB situations and level of physical activity between boys and girls, and logistic regression was carried out to verify the association of the situations with total SB (p <0.05). Results revealed that 47.5% of the adolescents spend more than 14 hours/day on SB (mean of 13.7 ± 3.4 hours/day). The situations associated with total SB were: smartphone (OR=6.23; p<0.001); computer/tablet and video game (OR=2.5; p=0.012); obligations (OR=2.43; p=0.009) and TV (OR=2.35; p=0.009). High SB prevalence was found, but there was no sociodemographic factor associated with this behavior. Additionally, smartphone use presented a greater association with high amount of time for total SB.

O objetivo do estudo foi analisar a prevalência, os fatores sociodemográficos e o comportamento sedentário (CS) associados as situações do CS (1) obrigações; 2) computador/tablet e videogame; 3) smartphone; 4) televisão; 5) CS total) de adolescentes de Rio Claro-SP. Participaram do estudo 482 adolescentes (14,4±2,1 anos) de 3 escolas públicas e 2 particulares, avaliados por um questionário de identificação, anamnese clínica e nível socioeconômico; Questionário de Comportamento Sedentário, com questões adicionais relacionadas ao CS e o uso de smartphones e videogames; Questionário de Atividade Física Habitual para Adolescentes; e mensuração do peso e estatura para o cálculo de Índice de Massa Corporal (IMC) (kg/m²). Realizou-se análise descritiva, teste t de Student para comparar as situações de CS e nível de atividade física entre meninos e meninas e regressão logística para verificar a associação das situações com o CS total (p<0,05). Identificou-se que 47,5% dos adolescentes permanecem mais de 14 horas/dia em CS (média de 13,7±3,4 horas/dia). As situações associados ao CS total foram: smartphone (RO=6,23; p<0,001); computador/tablet e videogame (RO=2,5; p=0,012); obrigações (RO=2,43; p=0,009) e televisão (RO=2,35; p=0,009). Relatou-se alta prevalência de CS, porém não houve nenhum fator sociodemográfico associado com esse comportamento. Adicionalmente, o uso do smartphone apresentou maior associação com o alto tempo de CS total.
PREVALÊNCIA E FATORES SOCIODEMOGRÁFICOS ASSOCIADOS AO COMPORTAMENTO SEDENTÁRIO EM ADOLESCENTES DE RIO CLARO-SP
Keywords: Sedentary lifestyle; Adolescent; Epidemiology; Estilo de vida sedentário; Adolescente; Epidemiologia